A first quantitative approach for detecting volumetric defects in additive manufactured metal samples by using active thermographic technique. Issue 1 (January 2022) - D'Accardi, Ester; Palumbo, Davide; Errico, Vito; Fusco, Andrea; Galietti, Umberto
Abstract: This work is focused on the quantitative analysis of defects produced in metal samples of AISI 316L with Laser Powder Bed Fusion (L-PBF) additive manufacturing (AM) process by means of active thermographic techniques. A simple and common set-up with 2 flash lamps and a cooled sensor has been used to analyse the differences between planar and volumetric defects. In particular, the presence of imprinted spheres containing inside non-sintered metallic powder has been compared with those of similar cylinders in size and depth, induced in similar samples. Furthermore, the differences in terms of thermal contrasts have been studied between the cylinder manufactured as an internal defect with powder inside, against the same geometry, but with a small channel for the discharge of the non-melted material. The analysis of the thermal signal and the application of post processing algorithms allowed us to identify the thermal features suitable for describing the behaviour of different kind of defects, typical of the process.